Anthropometric and cephalometric facial characteristics of adult Saudi patients with skeletal class III malocclusions - Nour M Almokri; Doaa H Alsaggaf; Fahad Faiz Alsulaimani; Khalid H Zawawi (Wolters Kluwer Medknow Publications, 2023)
Objectives: We aimed to assess adult Saudi patients' facial anthropometry and cephalometric characteristics with skeletal Class III malocclusions compared to Class I malocclusion patients. Materials and Methods: Our cross-sectional study included a review of the orthodontic records of 108 patients: 54 patients with skeletal Class III malocclusions and 54 patients with skeletal Class I malocclusions, equally distributed between males and females. Using anthropometric landmarks, seven angular and eight linear measurements were recorded and compared between Class III and Class I patients. In addition, we compared three horizontal facial proportions and three horizontal neoclassical canons between the two groups. Finally, we used Student's t-tests to compare continuous variables and Chi-square tests for categorical variables. Results: Class III patients had significantly larger mandibular length, mandibular plane angle, mid- and lower-anterior face height, and posterior face height (P < 0.05) compared to Class I patients. Class III patients had significantly proclined upper incisors, retroclined lower incisors, and an obtuse interincisal angle (P < 0.05). The mouth: nose ratio differed significantly between skeletal Class III and I patients (P = 0.008). The orbital canon was valid in 14.8% of Class I and 9.3% of Class III patients, respectively. The orbitonasal proportion applied only to 31.5% and 20.4% of Class I and III patients, respectively. The naso-oral canon occurred in 18.5% and 1.9% of Class I and III patients, respectively. Conclusion: Saudis with Class III skeletal profiles have some distinctive Class III characteristics not observed in most other ethnic groups. The established horizontal facial proportions, neoclassical facial canons, and Class III skeletal profile did not apply to Saudis with skeletal Class I malocclusions, indicating that these proportions and characteristics may not be suitable as references when planning the surgical treatment for these patients.